Perkembangan Konsep Manajemen Risiko dalam Literatur Pendidikan Islam Di Indonesia - Naufal Abdurrozaq; Wahyu Hidayat (ANNAHDLIYAH, 2026)
This study aims to map and analyze the conceptual evolution of Risk Management in Islamic Education in Indonesia. The research identifies the most dominant risk categories and investigates how Sharia values are integrated into Risk Management in Islamic Education. This mapping is vital for understanding how Islamic educational institutions respond to the challenges and complexities of the present era. The research employs a qualitative Systematic Literature Review as its methodology. This data was collected from textbooks and indexed journals (SINTA, Scopus, and repositories) concerning Islamic Education Management and Risk Management. Publications from 2010 to 2020 are included in this collection. To conduct data analysis, a qualitative model was used for data reduction, display, and the drawing of validated conclusions. The research shows that the idea of Risk Management in Islamic Education has evolved from a reactive and siloed approach to a more integrated approach for enterprise risk management. Currently, the most critical risks are academic (curriculum relevance), human resource risks (teacher competence), and, most importantly, ethical and moral risks. The inclusion of Sharia principles (Amanah and Tawakal) represents a major advancement, which places the protection of the spiritual and ethical mission as paramount. To strengthen institutions and ensure mission sustainability amidst fluctuating digital and moral challenges, an ethical and flexible Risk Management framework in Islamic Education is required.